Parenting During the Elementary School Years, Part 2: Discipline - Millie Ferrer; Ingrid Rivera; Anne M. Fugate (EDIS)
This document is FCS2203, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2002.